Eksplorasi Nilai Karakter Film Animasi Lorong Waktu sebagai Media Pembelajaran Drama di Sekolah Dasar - Putri Hapsari Ayuningtyas (Advances In Education Journal, 2025)
This research investigates the character valuesfound in the animated Lorong Waktu and its potential use in fourth-grade elemntary school drama lessons. Using a qualitative content analysis on six selected episodes Rantang Amanah, Terima Kasih Guru, Tolong menolong, Koruptor, Malas Belajar, and Ngeprank, the study identifies ten key character values; religiosity, honesty, discipline, hard work, independence, curiosity, love of reading, environmental care, social care, and responsibility. Among these, religiosity and responsibility are predominant. Because Lorong Waktu conveys important moral messages, the film is suitable for drama-based learning activities such as Ayo Bermain Peran and Ayo Mengamati. This research is limited to six episodes and does not explore students classroom responses. Practically, the findings can guide teachers in integrating character education through drama learning using animated media.